Periodontal health status in hospitalized cerebral palsy patients of rural Punjab - Anushi Mahajan; Santosh Mathangi; Gina Singh (Wolters Kluwer Medknow Publications, 2018)
Introduction: Cerebral palsy (CP) is an important neurological condition that originates in early childhood but affects individuals throughout the life. It leads to specific motor skill problems, delay in developmental milestones, and physical limitations such as abnormal muscle tonus, reflexes, and persistent infantile reflexes. Periodontal disease is the most prevalent oral condition in hospitalized CP patients. These patients are at a higher risk of periodontal disease due to physical and cognitive impairment. The lack of awareness and availability of oro dental care facilities in rural areas is also a hindrance in this regard. Objective: The objective of the present study was to evaluate the periodontal health status and treatment needs of hospitalized CP patients of rural Punjab. Methodology: Periodontal health status and treatment needs of hospitalized CP patients were determined by epidemiological indices. Questionnaires were filled by the patient's parents/attendants about the home-care oral hygiene measures and dietary habits of the patient. All patients were given nonsurgical periodontal therapy with reenforcement of oral hygiene measures as a part of our treatment plan. Results and Conclusion: From this study, it was concluded that periodontal disease is prevalent in hospitalized cerebral-palsied patients. Treatment needs for such patients include assisted oral health care, pain management, and constant psychosocial support. The inclusion of a dental healthcare professional in the management team would help improve the quality of life in these hospitalized cerebral-palsied patients.